Non-dioxin like polychlorinated biphenyl indicator congeners in Northwest Atlantic spiny dogfish (Squalus acanthias). Issue 1 (15th July 2017) - St-Gelais, Adam T.; Aeppli, Christoph; Burnell, Craig A.; Costa-Pierce, Barry A.
Abstract: In the Northwest Atlantic Ocean (NWAO), spiny dogfish ( Squalus acanthias ) is a promising commercial species following of collapse of traditional groundfish stocks. There are little available data assessing polychlorinated biphenyls (PCBs) in NWAO spiny dogfish. Here, six non-dioxin like PCB indicator congeners used in European Union regulations (EU NDL-PCB) were quantified via gas chromatography/mass spectrometry in 50 mature male spiny dogfish landed in southern New England. The average total concentration of EU NDL-PCBs was 58 ± 43 ng/g (mean ± 1 standard deviation). PCB values (corrected for co-elution) were below the 200 ng/g EU regulatory limit. Results provide first recent regional insight into the PCB content of spiny dogfish in the NWAO. However, our study offers only a snapshot of one particular dogfish population, and might not be representative for the whole NWAO. This study underscores the need for further testing in this species. Highlights: Little available data on polychlorinated biphenyls (PCBs) in NWAO spiny dogfish Assessed non-dioxin like PCB indicator congeners (European Union) The average total concentration of EU NDL-PCBs was 58 ± 43 ng/g (mean ± 1SD) First recent regional insight into the PCB content of spiny dogfish in the NWAO Limited scope of dataset underscores need for further testing in this species.